2017
DOI: 10.1002/celc.201700724
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of the Reaction Behavior of Silicon Negative Electrodes in a Bis(fluorosulfonyl)amide‐Based Ionic Liquid Electrolyte

Abstract: Excellent cycling performance of an electrode composed of silicon alone was achieved in a bis(fluorosulfonyl)amide (FSA)‐based electrolyte, with a high discharge capacity of 950 mA h g−1 observed even at the 500th cycle. To elucidate the reaction behavior of the Si electrode in an FSA‐based ionic liquid electrolyte, we investigated the change in the cross‐sectional morphology of the Si‐active material layer, the distribution of Li in the layer, and the crystallinity of Si on the electrode surface. By cross‐sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 21 publications
(47 citation statements)
references
References 35 publications
1
45
1
Order By: Relevance
“…In contrast, a surface film derived from ionic liquid electrolytes is homogeneous and thin. The lithiation of Si uniformly occurs in the ionic liquid electrolytes, which leads to the spread of the stress over the entire electrode surface . No accumulation of strain suppresses the severe disintegration of the Si electrode.…”
Section: Resultsmentioning
confidence: 84%
See 4 more Smart Citations
“…In contrast, a surface film derived from ionic liquid electrolytes is homogeneous and thin. The lithiation of Si uniformly occurs in the ionic liquid electrolytes, which leads to the spread of the stress over the entire electrode surface . No accumulation of strain suppresses the severe disintegration of the Si electrode.…”
Section: Resultsmentioning
confidence: 84%
“…This result demonstrates that the decomposition of the FSA anion (F 2 NO 4 S 2 ) occurs on the FeSi 2 electrode, whereas the Py13 cation (C 8 H 18 N) hardly decomposes. We previously reported that PC mainly decomposed on the cross‐section of the Si‐alone electrode, whereas no decomposition of LiTFSA occurred . Therefore, the properties (component, thickness, and so on) of the surface films formed on different electrodes should differ even in the same electrolyte.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations